Australian dentists: characteristics of those who employ or are willing to employ oral health therapists1. (20th May 2015) - Kempster, C; Luzzi, L; Roberts‐Thomson, K
Abstract: Background: There has been an increase in the availability of oral health therapists (OHTs) in the oral health workforce in the last decade. The impact these clinicians will have on the oral health of the general public is dependent on access pathways and utilization. This study aimed to profile Australian dentists who employ or are willing to employ OHTs and to explore the degree of association between dentist characteristics and employment decisions. Methods: This cross‐sectional study used a random sample of Australian dentists (n = 1169) from the Federal Australian Dental Association register in 2009. Participants were sent a postal questionnaire capturing dentist characteristics and oral health practitioner employment information. Results: An adjusted response rate of 55% was obtained. Dentists willing to employ OHTs included non‐metropolitan dentists, dentists in multiple surgery practices and those considering practice expansion. Age, gender and sector of practice were not significantly associated with retrospective employment decisions or willingness to employ in the future. Conclusions: Certain characteristics of dentists or of their practice are associated with their history of employment and willingness to employ OHTs. Employment decisions are more commonly related to entrepreneurial aspirations (expressed as a willingness to expand), sector of practice, surgery capacity and regionality over gender and age. Understanding the factors that influence the employment of OHTs is important in enhancing access pathways to the services provided by OHTs.